HUBUNGAN ANTARA KEPERCAYAAN DIRI DAN AKTUALISASI DIRI PADA KARYAWAN PT. DUTA MEDIA KALTIM PRESS (SAMARINDA POS) - Patioran, Desi Natalia (MOTIVASI, 2013)
This study aims to determine whether there is a significant positive relationship between self-confidence and self-actualization with the employees of PT. Duta Media Kaltim Press (Samarinda Post). The hypothesis that the proposed in this study is that there is a positive and significant relationship between self-confidence with self-actualization. Subjects in this study were employees of PT. Duta Media Kaltim Press (Samarinda Pos) with criteria editors position or title, precast or creative division, mountase, advertising, marketing and public or personnel totaling 60 subjects consisted of 47 male respondents and 13 female respondents. Scale used in this study is a scale of self-actualization that refers to those aspects of orientation is realistic, efficiently perceive reality, accept yourself, others and the environment for what it is, recognize the dignity of humanity, has a very creative and social interests that put forward by Maslow and confidence scale with aspects such as conviction self ability, optimistic, objective, rational and realistic responsible. The results showed a positive relationship between self-confidenceÂ with self-actualization, which is on the point of the analysis is the product moment correlation r = 0.523 (p <0.05), and the effective contribution of 43.4%. The hypothesis of this study stated in the thank.